The Effectiveness of Using Graphics Interchange Format (GIF) in Teaching Chemistry - Jules Mark Abgao (IJCER (International Journal of Chemistry Education Research), 2023)
The study utilized a quasi-experimental method of the pretest-posttest design with pre-selected groupings for the control and experimental groups. The study used validated researcher-constructed questionnaires to determine the student’s performance during the experimentation. A pretest was implemented for both groups prior to the implementation of the proposed interventions, with the experimental group exposed to online lectures with GIF-Enhanced Instructional Materials, while the control group utilized conventional online lectures. After the implementation of both interventions, a posttest was administered, and an attitude survey toward Chemistry. The findings showed that both groups had a significant improvement in terms of their performance from the pretest to the posttest, but the significant difference between the mean gains of both groups favored the experimental group. The experimental group was positive about the use of GIF in teaching Chemistry, while the control group somewhat agreed on the positive impact of Chemistry, while the experimental group agreed. In conclusion, using GIFs in online lectures proved to be more effective and impactful than conventional online lectures.